KEMAMPUAN LITERASI MEMBACA MELALUI PENGEMBAGAN MODEL PEMBELAJARAN KONSTRUKTIVISME MULTIMEDIA - Alfitriana Purba (JURNAL ILMU PENDIDIKAN, 2026)
The urgency of this research is to develop higher education learning technology by future needs, especially to achieve Indonesia Gold 2045 and the implementation of IKU/MBKM, by integrating culture, as advanced countries do not forget their ancestors. One of the cultures that need to be introduced and preserved by the younger generation. The research method used is the Research and Development approach with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model, with a sample of 35 Indonesian Language Education Study Program students focusing on reading literacy skills and cognitive aspects. The research instrument used is a Likert scale questionnaire to analyze the difficulties faced by students in achieving reading literacy skills. The results indicate that reading literacy, a weakness factor for students, is influenced by a factor named Reading Ease and a factor named Reading Activity Evaluation. Thus, it is necessary to implement learning activities that align with students' needs in developing individual capabilities for the future, specifically by developing a multimedia constructivist learning model.